Buildings Archaeology Without Recording - Dixon, James (Journal of Contemporary Archaeology, 2018)
This short paper outlines the development and operation of a workshop series called Buildings Archaeology Without Recording. The workshops are an experiment in an artistically-inspired site-specific archaeology, which has proven successful in public and local-political engagements with archaeological themes.